(3TQM CSeGA Cgd HOQs - (3GdMafj , eMeO Hf SGde Hf CMeO GdMafj, TeS GdOjf,J (B1181 (3g` s
(3ChdgG (B:s
(3CeG HYO bO CWdYJ Ydi JCdja eJYdbg HCSeGA Cgd HOQ , aefgG eG ajg JbUjQ hefgG eG ajg JWhjd aJYdb NGWQI HPcQ eNJUQ CbJUQ ajg Ydi JMQjQ VHWgG s
(3BNQgG (B:s
(3Rjf Hf GdeRjf , HVe Gdeje haJM GdRGi BNQg fhf eUZQG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B134 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B15s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B248 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(9271 (3M(B) s
Keywords: (3GdJGQjNs